Disparate Associations of 24-h Central Aortic and Brachial Cuff Blood Pressure With Hypertension-Mediated Organ Damage and Cardiovascular Risk - Hu, Yueliang; Zhao, Jiehui; Wang, Qian; Chao, Huijuan; Tang, Biwen; Cheng, Di; Tan, Isabella; Butlin, Mark; Avolio, Alberto; Wang, Weiliang; Zuo, Junli (Frontiers in Cardiovascular Medicine, 2022)
Objective Aim of this study was to evaluate the associations of non-invasive central aortic and peripheral (brachial) blood pressure (BP) for Hypertension-mediated organ damage (HMOD) and atherosclerotic cardiovascular disease (ASCVD) risk. Methods We evaluated associations of HMOD with 24-h ambulatory blood pressure monitoring (ABPM) of central aortic and peripheral BP indices in patients with primary hypertension and presence of several cardiovascular risk factors. BP measurements were performed by means of a non-invasive automated oscillometric device (Mobil-O-Graph). HMOD was defined as the presence of carotid intima-media thickness (IMT) above normal values and/or carotid plaque, left ventricular hypertrophy (LVH), and/or renal abnormalities as assessed by urine albumin/creatinine ratio above normal values and/or estimated glomerular filtration rate (eGFR) <60 ml/min per 1.73 m2. Results In the study cohort of 273 (age 55.2 ± 13.4 years, 71.8% male) patients with primary hypertension, documented HMOD was present in 180 (65.9%), LVH in 70 (25.6%), increased IMT in 129 (47.3%). Fifty-six patients (20.5%) had kidney organ damage (20.5% albuminuria and 2.6% impaired eGFR). When accounting for confounding factors (age, sex, body-mass-index, antihypertensive treatment, smoking, triacylglycerol, statin treatment, glucose, hypoglycemic therapy, or heart rate) only peripheral 24-h pulse pressure (PP) maintained statistical significance with HMOD indices (OR: 1.126, 95% CI: 1.012~1.253; p = 0.029). Using ASCVD risk score as the independent continuous variable in multiple linear regression, 24-h central systolic pressure (SBP) (β = 0.179; 95% CI:0.019~0.387; p = 0.031), daytime central PP (β = 0.114; 95% CI:0.070~0.375; p = 0.005, night-time central SBP (β = 0.411; 95% CI:0.112~0.691; p = 0.007) and night-time PP (β = 0.257; 95% CI:0.165~0.780; p = 0.003) were all positively associated with ASCVD risk. Conclusions Blood pressure obtained by 24-h ABPM was better correlated with HMOD than office BP. Whilst 24-h peripheral BP showed a stronger association with HMOD than 24-h central BP, the prognostic value of 24-h central BP for the 10-year ASCVD risk was superior to 24-h peripheral BP.